Gender disparity in academic performance of students in the Faculty of Agriculture and Forestry, University of Ibadan, Oyo State (2017)
Gender disparity in schooling is observed among younger population in which men perform better than women in certain settings while women outperform men in other settings. This study examined gender disparity in academic performance among faculty of agriculture and forestry students of University of Ibadan. One hundred and fifty respondents were randomly selected from 200, 300 and 400 levels and structured questionnaire was used for data collection. Data were analysed using descriptive statistics such as frequencies and percentages while T-test was employed for inferential statistics. Results show that majority of the respondents were within the active age of 18-26 years (88.0%), single (86.7%) and were from monogamous family (71.3%). Conduciveness of learning environment (0.44) and parental/guardian attention (0.44) were considered by both male and female students respectively as the major factors that affect academic performance. About 45.2% of male students and Female students had positive attitude to education (53.2%) and larger percentage of female students were in 2nd class upper division (48.1%). Furthermore, there was a significant difference in the academic performance of male (3.9863) and female (4.5870) students (t=6.049, p=0.015). The study concluded that female students perform academically better than their male counterparts. Male students should be given optimum attention in gender mainstreaming advocacy.